Experimental Study on MICP Technology for Strengthening Tail Sand under a Seepage Field - Zhi-jun Zhang; Biao Li; Lin Hu; Huai-miao Zheng; Gui-cheng He; Qing Yu; Ling-ling Wu (Geofluids)
Microbial-induced calcium carbonate precipitation (MICP) technology is a new green reinforcing technology in soil stabilization. Targeting on the problem that seepage is the main factor of causing the instability of a tailings dam, a comparative experiment is conducted, which includes the MICP technology on reinforcing tailings with or without the effect of a seepage field. The results of the comparative experiment are as follow: the mercury penetration test indicates that, under the function of a seepage field, the total pore in the tailing is relatively decreased; SEM shows that under the function of a seepage field, the intergranular pore increases; the direct shear test shows that under the function of a seepage field, the tailings’ shear strength decreases; the determination of calcium ion content shows that the distribution of calcium carbonate in the tailings under the action of a seepage field is more uneven.